Endorsement Sebagai Trend Pemasaran Modern Melalui Media Sosial Pada Akun Instagram Awkarin - Dewi Untari; Sari Sri Handani (LPPM STIKes SITI HAJAR dan Insight Power, 2022)
The purpose of this study was to determine endorsement as a modern social media marketing trend. This research used a descriptive type of approach using a qualitative approach. The research subject is the Awkarin Online Shop Seller who is asked to provide information about a fact or opinion. The results of the researchers in this study are in accordance with the research conducted, namely Awkarin has 4 million Instagram followers, and is dominated by young people. Few have read the newspapers or heard the radio before seeing the advertisements. In addition, the television industry is increasingly widespread, so that the ease of changing channels makes people lazy to wait for advertisements from Endors to become a trend in marketing products, and there are many advantages of endorsers compared to commercial advertisements. Endorsements or endorsements are one of the new trends in generating more dynamic marketing strategies that are more effective for increasing sales. Endorsements are a form of advertising revolution, in a more personal way. Because endorsed goods are usually made as if they are goods that seem more natural than commercial advertisements. In addition, endorsement is one way to build public trust and endorsers make the sales value increase.